2019
DOI: 10.35379/cusosbil.588230
|View full text |Cite
|
Sign up to set email alerts
|

“Resilience” Kavramina Örgüt Bağlaminda Türkçe Karşilik Öneri̇leri̇

Abstract: Bu çalışmada, sosyoloji, psikoloji, işletme ve çeşitli mühendislik alanlarında kullanılan "resilience" kavramına, işletme yönetimi ve endüstri mühendisliği alanlarındaki çalışmalarda kullanılmak üzere örgüt bağlamında Türkçe bir karşılık önerilmesi amaçlanmıştır. Esneklik, geri sıçrama, eski haline dönme ve uyum sağlayabilme gibi anlamları bulunan "resilience" kavramının farklı yaklaşımlar çerçevesinde aynı anlamda kullanılmadığı görülmüştür. Söz konusu kavramın farklı anlamlarda kullanılması, Türkçe çalışmala… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…In subsequent years, it is seen that Mallak (1998) contributed to the conceptualization of the expression of organizational resilience. Gerçek and Börekçi (2019) stated that the concept of resilience in the organizational context refers to the ability of an organization to heal, adapt, and transform. It can be said that the development of this ability depends on many factors.…”
Section: Organizational Resiliencementioning
confidence: 99%
“…In subsequent years, it is seen that Mallak (1998) contributed to the conceptualization of the expression of organizational resilience. Gerçek and Börekçi (2019) stated that the concept of resilience in the organizational context refers to the ability of an organization to heal, adapt, and transform. It can be said that the development of this ability depends on many factors.…”
Section: Organizational Resiliencementioning
confidence: 99%
“…It is seen that the words strength and durability are also used in the literature instead of resilience (Gizir, 2004;Öz & Bahadır Yılmaz, 2009;Yıldırım, 2016;İşcan & Malkoç, 2017). In international studies, the way in which the concept of "resilience" is handled is differentiated by adding another determinant word in front of this word (e.g., psychological resilience, organizational resilience, career resilience), but it has been observed that different words are preferred in studies originating from Turkey (Yılmaz Börekçi & Gerçek, 2018). Stewart, Reid and Mangham (1997) defined resilience as an individual's ability or capacity to cope effectively when faced with significant changes, negative or risky situations in his life.…”
Section: Introductionmentioning
confidence: 99%
“…The recovery capabilities of organizations help them survive and their ability to adapt and transform contributes to sustainability. In other words, resilience refers to the ability of organizations to recover from the "wounds" they have received during disasters and to maintain their lives (Gerçek & Börekçi, 2019).…”
Section: Introductionmentioning
confidence: 99%